2021
DOI: 10.1002/pros.24181
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐year trends in prostate cancer stage and grade migration in a large contemporary german radical prostatectomy cohort

Abstract: Background: A trend towards inverse stage migration in prostate cancer (PCa) was reported. However, previous analyses did not take into account potential differences in sampling strategies (number of biopsy cores), which might have confounded these reports.Material and Methods: Within our single-institutional database we identified PCa patients treated with radical prostatectomy (RP) between 2000 and 2020 (n = 21,646). We calculated the estimated annual percentage change (EAPC) for D'Amico risk groups, biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
(58 reference statements)
2
9
0
2
Order By: Relevance
“…Last but not least, SEER represents a retrospective data repository. Although, no prospective trial addressed the end points of the current study, several large institutional databases relied on prospective gathered data on biopsy and pathologic findings 33 . Such databases are undoubtedly better.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, SEER represents a retrospective data repository. Although, no prospective trial addressed the end points of the current study, several large institutional databases relied on prospective gathered data on biopsy and pathologic findings 33 . Such databases are undoubtedly better.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, differences in RP rates over time in transplant patients were estimated with estimated annual percent change (EAPC) that relied on log-linear methodology, as previously reported. [19][20][21] All tests were two sided with a level of significance set at p < 0.05 and R software environment for statistical computing and graphics (version 3.4.3) was used for all analyses.…”
Section: Discussionmentioning
confidence: 99%
“…While the percentage of GS6 cases undergoing prostatectomy is difficult to measure directly, it can be inferred that this has declined. Large cohort studies have shown a reduction in the prevalence of GS6 cancer at prostatectomy in the United States to one-third of its prior incidence (to 10%) [6], and in Europe to one-half its prior incidence (to 8.3%) [7]. Renaming GS6 cancer as non-cancer is unlikely to mitigate overtreatment while discouraging a subset of patients from undergoing active surveillance, including multiparametric MRI and repeat biopsy.…”
mentioning
confidence: 99%